Detection of occult hepatitis B and window period infection among blood donors by individual donation nucleic acid testing in a tertiary care center in South India. (16th November 2016) - Keechilot, Cinzia S.; Shenoy, Veena; Kumar, Anil; Biswas, Lalitha; Vijayrajratnam, Sukhithasri; Dinesh, Kavitha; Nair, Prem
Abstract : With the introduction of highly sensitive hepatitis B surface antigen immunoassay, transfusion associated HBV infection have reduced drastically but they still tend to occur due to blood donors with occult hepatitis B infection (OBI) and window period (WP) infection. Sera from, 24338 healthy voluntary blood donors were screened for HBsAg, HIV and HCV antibody using Vitros Enhanced Chemiluminescent Immunoassay. The median age of the donor population was 30 (range 18–54) with male preponderance (98%). All serologically negative samples were screened by nucleic acid testing (NAT) for viral DNA and RNA. NAT-positive samples were subjected to discriminatory NAT for HBV, HCV, and HIV and all samples positive for HBV DNA were tested for anti-HBc, anti-HBs, HBeAg. Viral load was determined using artus HBV RG PCR Kit. Of the 24, 338 donors screened, 99.81% (24292/24338) were HBsAg negative of which NAT was positive for HBV DNA in 0.0205% (5/24292) donors. Four NAT positive donors had viral load of <200 IU/ml making them true cases of OBI. One NAT positive donor was negative for all antibodies making it a case of WP infection. Among OBI donors, 75% (3/4) were immune and all were negative for HBeAg. Precise HBV viral load could not be determined in all (5/5) NAT positive donors due to viral loads below the detection limit of the artus HBV RG PCR Kit. The overall incidence of OBI and WP infections was found to be low at 1 in 6503 and 1 in 24214 donations, respectively. More studies are needed to determine the actual burden of WP infections in Indian blood donors.